A Data-Driven Method for Decision Support Systems in Mass Production and Mass Customization - Yetis, Hasan; Karakose, Mehmet (Ieee, 2018)
With the development of the concept of industry 4.0, mass customization is getting popularity nowadays. But because the mass customization, which allows customers to customize their products, needs more money and time, mass production is more preferred production type still. In this study, using the order data obtained from mass customization, a decision support system is aimed. The proposed decision support system can be used to determine the characteristics of the mass-production product, as well as in the ordering stage of mass customization. With the method, it is expected to increase sales of mass-produced products and increase the satisfaction of customers who give order for mass customization through the interface.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: mass customization; mass production; data mining; decision support system; recommendation system